Pengaruh ROA, BOPO, dan FDR Terhadap Tingkat Bagi Hasil Deposito Mudharabah - Hani Dwi Yuliana; Wirman (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
The purpose of this study was to determine the effect of ROA, BOPO, and FDR on the profit sharing rate of mudharabah deposits at islamic commercial banks in Indonesia from 2016 to 2019. The population this study were all Islamic commercial banks that have been registered with Bank Indonesia. The population of this study were 11 Islamic banks and the total sample used was 4 banks. The analysis technique used by researchers is multiple linear regression. In this study, the hypothesis test used is the t-test to test the partial regression coefficient and the f-test to test significance simultaneously with a significance level of 5%. The results in this study indicate that ROA has a significant effect on the profit sharing rate of mudharabah deposits and ROA, BOPO, FDR simultaneously have a significant effect on the profit sharing rate of mudharabah deposits.